The impact of prenatal care quality on neonatal, infant and child mortality in Zimbabwe: Evidence from the demographic and health surveys - Makate, Marshall; Makate, C. (Oxford University Press, 2017)
© The Author 2016. The impact of the quality of prenatal care on child mortality outcomes has received less attention in sub-Saharan Africa. This study endeavoured to explore the effect of the quality of prenatal care and its individual components on neonatal, infant and under-five mortality. The empirical analysis uses data from the three most recent waves of the nationally representative Demographic and Health Survey for Zimbabwe conducted in 1999, 2005/06 and 2010/11. The results indicate that a one-unit increase in the quality of prenatal care lowers the prospect of neonatal, infant and under-five mortality by approximately 42.33, 30.86 and 28.65%, respectively. These findings remained roughly the same even after adjusting for potential mediating factors. Examining the effect of individual prenatal care components on child mortality revealed that women who receive information on possible complications arising during pregnancy are less liable to experience a neonatal death. Similarly, women who had blood pressure checks and tetanus immunizations were less likely to experience an infant or under-five death. We did not find any statistically meaningful impact on child mortality outcomes of blood and urine sample checks, iron tablet consumption, and the receipt of malarial tablets. Overall, our results suggest the need for public health policymakers to focus on ensuring high-quality prenatal care to enhance the survival prospects of Zimbabwe's infants.